Effect of Temperature and Salinity on the Infectivity Pattern of White Spot Syndrome Virus (WSSV) in Giant tiger shrimp Penaeus monodon (Fabricius 1837) - Raj, Stalin; Vijayan, K. K.; Alavandi, S. V.; Balasubramanian, C. P.; Santiago, T. C. (Indian Journal of Fisheries, 2012)
White spot disease (WSD) caused by the lethal white spot syndrome virus (WSSV) continues to be the major cause ofmortality among farmed tiger shrimp in India and elsewhere, resulting in an annual loss of about 4-6 billion US$. Among theenvironmental variables, temperature and salinity of the rearing water are considered to be major triggering factors for whitespot disease outbreak. In order to characterise the effect of salinity and temperature on the pathogenecity of WSSV infectionin giant tiger shrimp Penaeus monodon, a laboratory challenge study was conducted at different levels of temperature(16, 25, 27, 28, 30, 32 and 36 ÂºC) and salinity (0.5, 5, 10, 15, 30 and 45 g l-1) with virulent white spot syndrome virus.Significant influence of temperature (p